Biologic studies of Copitarsia sp. (Lepidoptera: Noctuidae) under insectarium conditions - CARDONA-C., DIEGO A.; LONDOÑO-Z., MARTHA E.; JARAMILLO-N., JORGE E. (Revista Colombiana de Entomología, 2004)
The c.rucifers are an important source of fiber and vitamins in the  Colombian diet. Their production is affected by pests like Copitarsia sp.. which causes damage to the head or florets of the plant. In this study, parameters like fecundity, fertility, mortality, sex ratio and life cycle of Copitarsia sp. were analyzed because they will support pest management. The study was conducted in  ICA "Tulio Ospina" located in Bello, Antioquia under natural conditlons of temperature and relative humidity. The adults used to study fecundity were introduced into glass flasks that contained accordion paper used for oviposition. The life cycle began with a cohort of 407 eggs, which were kept in individual plastic containers. Each female lay an average of 550,5 eggs, which had fertility of 92,87%. The sex ratio was  1: 1  The accumulated mortality in all the developmental stages was 38,82%. The life cycle from egg to adult was 45,94 ± 2,5 days. Egg incubation was 5,037 ± 0,21 days. The larval period had 5 or 6 instars, with partial durations of L 1  3,80 ± 0,73 days. L2 2.80 ± 0,55 days, L3 2.97 ± 0,70 days, L4 3, 12 ± 0,80 days, L5 4,91 ±  1,60 days and L6 5,55 ±  0,35 days; the prepupa and pupa had durations of 2,40 ±  0,62 days and 19,26 ±  1, 16 days, respectively, and the adult 15,26 ± 5,37 days.